Internalisasi Nilai-Nilai Pendidikan Akhlak pada Anak Usia Dini melalui Media Buku Balita Berakhlak Mulia - Ulpaini Roudhotur Rohima; Muru'atul Afifah; Yusfar Ramadhan (Fakta: Jurnal Pendidikan Agama Islam, 2022)
This study discusses the importance of instilling moral education in early childhood, where at this time children experience a golden age in their development, children easily learn from the environment. So that at this time is the most appropriate time to internalize the values of moral education into children's identities with a variety of media, one of which is story books. The purpose of this study is to determine the process of internalizing the values of moral education contained in the book "Toddlers with noble character" in early childhood and to find out the supporting and inhibiting factors in internalizing the educational values of the book. The method used in this research is descriptive qualitative method, with data collection techniques through interviews, documentation and observation. The results of the research on the internalization process used the telling method, the advice, method, the reward method and the dialogue method. Supporting factors 1) family,helping to improve children’s moral education 2) The language of the books that are easy and have a lot of use,  3) Media from BBM books,in the from of hand puppets, posters and moral cards 4) manual books for parents for parents,help how to internalize BBM books  5) The inspirational story books of Rasulallah SAW., while the inhibiting factors are 1) busyness of parents, 2) lack of experience about the stories of Rasulallah SAW.